HUBUNGAN KUANTITAS TIDUR DENGAN KONSENTRASI BELAJAR REMAJA DI PONDOK PESANTREN MADINATUNNAJAH TANGERANG SELATAN - Riswahyuni Widhawati; Sivi Amiati Maryadi; Airin Yulistani (STIKes IMC Bintaro, 2020)
Sarwono explained that adolescence is a period of transitions of older adults, marked by the development of biological, psychological, moral, religious, social and cognitive. Individuals are required to meet basic human needs in order to sustain his life. One of the basic needs that diperlukn is sleep which is the basic necessities needed by everyone. Everyone needs sleep so that your body can function normally. On the condition of sleep, the body conducting the recovery process to restore the stamina of the body to be in optimal conditions. Concentration is the ability to focus the mind, feelings, will and our five senses on one object so that the individual can understand and understand object that diperhatikannya without thinking of other things. The goal in this research is to know the influence of the relationship of the quantity of sleeping with a concentration of study in teen boarding ponsok madinatunnajah. Type of this research is Quantitative with the research Crossectional . Population studies as much as 70 teens with Samples rendem sampling. Methods of data analysis using Chi Square. The results of the Research showed a p value 0.00. Conclusion: there is an influence quantity relationship sleeping with a concentration of study.